Fatty acids and the regulation of pyruvate dehydrogenase interconversion - Stewart, M; Stewart, Melanie Ann (1997)
﻿ This thesis presents evidence for a novel mechanism of regulation of pyruvate dehydrogenase (PDH) kinase by fatty acids and also results of a study of muscle triacylglycerol concentration. In animals regulation of PDH complex activity is central to the selection of respiratory fuels and to the conservation of glucose during carbohydrate deprivation. The principal means of regulation of PDH complex is interconversion of phosphorylated (inactive) and dephosphorylated (active) forms effected by PDH kinase and PDH phosphatase. Earlier in vitro studies by others had identified both shorter term (min) and longer term (hours) mechanisms of activation of PDH kinase by fatty acid. In the present study PDH kinase activity (as measured by rates of ATP-dependent inactivation of PDH complex in extracts) was shown to be increased when rat heart mitochondria were incubated with palmitoyl-L-carnitine [PC] (and other CoA utilising respiratory substrates). The activation of PDH kinase persisted through removal of respiratory substrate following incubation with CCCP. A comparable effect of PC was also demonstrable in heart mitochondria from 48h-starved rats (i.e. the mechanism may be distinct from that which increases PDH kinase activity in starvation). Rates of ATP-dependent inactivation of PDH complex were also increased when extracts of rat heart mitochondria were incubated with palmitoyl-CoA (PCoA); the increase was comparable with that seen on incubation of intact mitochondria with PC. The PC effect in intact mitochondria and the PCoA effect in mitochondrial extracts may not be identical as PCoA further increased PDH kinase activity in extracts from mitochondria incubated with PC. Rates of incorporation of 32P from [γ-32 A method was developed and evaluated for measurement of triacylglycerol in rat soleus muscle strips with the object of investigating factors that may regulate triacylglycerol synthesis in this muscle. This study was abandoned because, although the method was highly reproducible, great variation was found in the triacylglycerol concentration of individual muscles suggesting the possibility of variable contamination with small amounts of adipose tissue.